Sustaining ethical ePortfolio practices: Insights from AAEEBL’s Task Force Year 4 - Slade, Christine; Zurhellen, Sarah; Conefrey, Theresa (Journal of University Teaching and Learning Practice, 2025)
This paper recognises the importance of digital ethics when using ePortfolios and provides information about the development of a comprehensive resource from the Association for Authentic, Experiential and Evidence-based Learning (AAEEBL) Digital Ethics in ePortfolios Task Force’s four-year work. With the public release of ChatGPT addressing ethical challenges in education is critical. Over three years, the global Task Force diligently drafted, refined, and published a suite of digital ethics principles, strategies, scenarios, and resources, which is available as open source. In the fourth year (July 2022-June 2023), the Task Force formed three sub-groups to manage the growing number of objectives. The Development group explored intersections between principles and generative artificial intelligence (GenAI), while evaluating data responsibility. The Outreach group disseminated the work through engaging workshops and publications, which also allowed the wider community feedback opportunities to further enhance the resources. Furthermore, the Research group undertook the ePortfolio Mapping Project to shed light on labour dynamics within ePortfolio practice across North America. The survey instrument was then adapted for data collection in Australia, and New Zealand. The paper highlights the significant achievements of these collective efforts, shares preliminary research findings, and offers valuable insights. It aims to promote ethical ePortfolio usage to enhance teaching, learning and assessment. Practitioner Notes • Recognising potential ethical challenges in digital learning is critical. • ePortfolios enable integrated learning experiences to meet a range of pedagogical objectives, including the tracking of learning processes as well as end artefacts. • Learning how to apply ethical decision-making in using ePortfolios is essential. • Comprehensive resources have been developed to assist educators, students, professional staff, and other digital pedagogy stakeholders. • Research is underway into current ePortfolio practices which will inform future thinking, advocacy, and awareness.